IMPROVING THE STUDENTS' NUMERICAL LITERACY SKILLS BY USING INTERACTIVE MATHEMATICAL COMICS ON PYTHAGOREAN THEOREM: Meningkatkan Kemampuan Literasi Numerasi Siswa Menggunakan Komik Matematika Interaktif Pada Materi Teorema Phytagoras - Verra Arischa Kustantina; Nuryadi Nuryadi; Nafida Hetty Marhaeni (Pimpinan Cabang Muhammadiyah Kramat Jati, 2022)
This study aims to determine improving the students' numeracy literacy skills by using interactive mathematical comics on pythagorean theorem. This type of research is experimental research with pretest posttest control group design. The sample in this study was class VIIIA as the experimental class totaling 21 students and class VIIIB as the control class totaling 19 students. Data collection techniques used interviews, observations, and questions pretest and posttest of students' numeracy literacy abilities. The results showed that the use of mathematical comics was effective in increasing students' numeracy literacy skills. This is because mathematical comics are presented based on interesting story concepts, interactive forms of daily conversation so that they can increase students' learning motivation. In math comics, the questions presented also stimulate students' numeracy literacy skills because they are presented with information in the form of numbers, data, and symbols related to mathematics. In addition, by learning to use mathematical comics students are required to be able to analyze various information in the form of graphs, tables, charts, and the ability to draw conclusions. Therefore, this study concludes that the use of mathematical comics in mathematics learning is effective in improving students' numeracy literacy skills.